Electrochemical Performance of LiMn2O4/LiFePO4 Blend Cathodes for Lithium Ion Batteries - Qiu, Chengguang; Liu, Lina; Du, Fei; Yang, Xu; Wang, Chunzhong; Chen, Gang; Wei, Yingjin (Chemical research in Chinese universities, 2015)
A series of LiMn2O4/LiFePO4 blend cathodes was prepared by hand milling and ball milling in order to compensate the disadvantage of spinel LiMnaO4 and olivine LiFePO4. The morphologies of the blends were studied by scanning electron microscopy, and their electrochemical properties were studied by charge-discharge cycling, cyclic voltarnmetry and electrochemical impedance spectroscopy. It is easy to obtain uniform LiMn2Oa/LiFePO4 blends by the hand milling technique, while significant particle agglomeration is caused by the ball milling technique. When the LiMn2O4：LiFePO4 mass ratio is 1：1, the nano-sized LiFePO4 powders not only uniformly cover the micron-sized LiMn2O4 particles but also effectively fill in the cavities of the LiMn2O4 space. Such morphology offers a good electrical contact and a high tap density, which leads to a high discharge capacity and good cycle stability.